Совершенствование свойств фторопластоматричных углеволокнистых композитов путем влияния на параметры технологии их получения - Руденко, П. В.; Бурмистр, М. В.; Будник, А. Ф. (Eastern-European Journal of Enterprise Technologies, 2009)
Тhe article covers the issue choosing the mixing equipment for production of composites by the method of dry mixing a polytetrafluoroethylene matrix with a carbon fiber filler. It presents an analysis of influence different factors exert on the technological process of producing a high quality mixture of a polymeric composite. Key words: carbon fiber, mixing, polytetrafluoroethylene, polymer composite, quality